“PENGARUH PRODUCT QUALITY DAN SERVICE QUALITY TERHADAP LOYALITAS PELANGGAN BMW PT ASTRA INTERNATIONAL Tbk SUNTER (STUDI KASUS : JOY IS BMW)” - Ardiansyah, Avyndra (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2025)
This study aims to determine the effect of product quality on customer loyalty. The research method used in this research is descriptive method. The study population was BMW PT Astra International, Tbk customers 350 people and obtained a sample of 187 people using the Slovin formula. The data analysis method used is statistical analysis in the form of multiple linear regression tests using SPSS version 19 windows. The results show that product quality is positive and significant towards customer loyalty. Service quality is positive and significant towards customer loyalty. This is evidenced by the results of hypothesis testing (t test) which shows the values of the independent variables.